The Role of Electrifying Agriculture Marketing in Electricity Sales, Customer Growth, and Power Addition at PLN ULP Lakawan - Asriadi; Fitriani Latief; Andi Widiawati (SAFE-Network, 2026)
This study aims to analyze the influence of Electrifying Agriculture marketing on electricity sales, customer growth, and power addition at PT PLN (Persero) ULP Lakawan. The Electrifying Agriculture program is a marketing strategy for the productive sector that is directed to increase electricity utilization in the agricultural sector through economic value creation and operational efficiency. This research is based on Marketing Management Theory which emphasizes the importance of value creation and demand management in generating market responses. This study uses a quantitative approach with a survey method through the distribution of questionnaires to customers in the productive sector, especially the agricultural sector. The sampling technique used Stratified Random Sampling with a sample of 100 respondents determined using the Slovin formula. The data obtained was analyzed using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The results of the study show that Electrifying Agriculture marketing has a positive and significant effect on all dependent variables. The influence on electricity sales has a coefficient of 0.819 with a t-statistic value of 13.001 and a p-value of 0.000. The influence on customer growth has a coefficient of 0.730 with a t-statistic value of 8.610 and a p-value of 0.000. Meanwhile, the effect on power addition has a coefficient of 0.802 with a t-statistic value of 10.057 and a p-value of 0.000. The conclusion of this study shows that Electrifying Agriculture marketing plays a strategic role in increasing electricity consumption in the agricultural sector, expanding the customer base, and encouraging an increase in customer power capacity at PLN ULP Lakawan.